2013
DOI: 10.1002/pen.23777
|View full text |Cite
|
Sign up to set email alerts
|

Morphology–properties relationship in high‐renewable content polyurethanes

Abstract: The effect of diisocyanate nature and hard segment content on the morphology and properties of high‐renewable content segmented thermoplastic polyurethanes was studied. Vegetable oil‐based polyether diol and corn sugar derived chain extender were used as renewable reactants together with an aliphatic (1,6‐hexamethylene diisocyanate, HDI) or aromatic (4,4′‐diphenylmethane diisocyanate, MDI) diisocyanate as hard segment. Segmented thermoplastic polyurethanes were synthesized by two‐step bulk polymerization. Morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…Besides, biopolyurethanes show a band around 1728 cm À1 which encompasses LDI and CO3 carbonyl groups. In the same way, a shoulder ascribed to the carbonyl of urethane group was seen between 1705 and 1682 cm À1 [31], which becomes more intense as diisocyanate content increases, due to a higher amount of urethane groups per volume unit.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Besides, biopolyurethanes show a band around 1728 cm À1 which encompasses LDI and CO3 carbonyl groups. In the same way, a shoulder ascribed to the carbonyl of urethane group was seen between 1705 and 1682 cm À1 [31], which becomes more intense as diisocyanate content increases, due to a higher amount of urethane groups per volume unit.…”
Section: Resultsmentioning
confidence: 74%
“…It was seen that M w and M n decreased with the increase of LDI/PD content, due to the lower proportion of CO3 (the reagent with the higher molar mass) involved in the synthesis of the biopolyurethanes with higher LDI/PD content. In addition, the increase observed in PI can be attributed to vitrification, which hinders chain extension [31]. In any case, the variations on the molecular weight can be ascribed to segment architecture [32].…”
Section: Resultsmentioning
confidence: 97%
“…TgSS peaks [25] like in blocks based on HDI or MDI [5,26]. Soft domain glass transition temperature (T gSS ), melting temperature (T mSS ) and enthalpy ( H mSS ) of the synthesized WBPUs are summarized in Table 3.…”
Section: Samplementioning
confidence: 99%
“…The authors confirmed that aliphatic diisocyanate‐based polyurethanes showed more phase separation than the polyurethanes obtained with the use of aliphatic diisocyanates. Ugarte et al produced poly(ether‐urethane)s with the use of two different diisocyanates, for example, HDI and MDI. The authors found that the polyurethane prepared by using aromatic diisocyanate and a chain extender displayed enhanced stiffness and hardness, and lower elongation at break.…”
Section: Introductionmentioning
confidence: 99%
“…This was due to the increased number of physical crosslinking sites and spherulitic morphology of HS crystalline domains. However, materials prepared with the use of linear aliphatic diisocyanates exhibited fibrillary morphology of HS crystal microdomains . To investigate hydrogen bonding distribution and microphase separation, researchers used DSC and FTIR spectroscopy .…”
Section: Introductionmentioning
confidence: 99%